KAJIAN RENCANA PEMBANGUNAN PASAR INDUK BAHAN POKOK HASIL PERTANIAN DI KELURAHAN LUBUK BUAYA KECAMATAN KOTO TANGAH KOTA PADANG BERDASARKAN RENCANA TATA RUANG WILAYAH KOTA PADANG TAHUN 2010-2030 - Dilla Marfa Wanni; Yurni Suasti (JURNAL BUANA, 2019)
This study purpose to describe the suitability of the development plan for the parent market for agricultural raw materials in Lubuk Buaya, Padang City. The location of the construction of the main raw material for agricultural products is planned next to Pasar Lubuk Buaya, which is on land used by fruit traders now. This type of research is qualitative descriptive. The research subjects were determined by purposive sampling technique consisting of one Secretary of the Padang City Trade Office, 28 traders, and three suppliers. This study found that the planned development of the main market for agricultural raw materials in Lubuk Buaya was not suitable to be implemented because in terms of Lubuk Buaya locations it was too far from the markets in Padang City. So that it requires a longer travel time and affects the costs incurred. Another factor is the anxiety that the planned selling price in the wholesale market will be higher than it is now. This is because many purchases of agriultural staples are now carried out directly to the source area of goods and through telephone ordering.